Current views on N-glycolylneuraminic acid in therapeutic recombinant proteins. (November 2021) - Mastrangeli, Renato; Audino, Maria Concetta; Palinsky, Wolf; Broly, Hervé; Bierau, Horst
Abstract : The incorporation of the non-human N -glycolylneuraminic acid (Neu5Gc) in therapeutic recombinant proteins raises clinical concerns due to its immunogenic potential and the high prevalence of pre-existing anti-Neu5Gc antibodies in humans. The scientific literature is ambiguous regarding the actual impact of Neu5Gc-containing biotherapeutics as no severe adverse clinical manifestations were unequivocally attributed to Neu5Gc for currently marketed biotherapeutics. This review discusses structural and functional considerations of Neu5Gc-containing glycans regarding the potential impact on drug clearance, their recognition by pre-existing antibodies, and recent hypotheses regarding the tolerance to low Neu5Gc levels. Furthermore, it provides recommendations regarding the standardization of analysis and reporting, analytical aspects relevant for assessing risks associated with Neu5Gc-containing biotherapeutics, and approaches to minimize Neu5Gc incorporation in recombinant protein manufacturing. Highlights: Glycosylated biotherapeutics can contain the non-human N -glycolylneuraminic acid (Neu5Gc). Neu5Gc is a critical quality attribute because it raises clinical concerns due to its immunogenic potential as well as the high prevalence of pre-existing anti-Neu5Gc antibodies in humans. An adequate risk assessment should be based on a comprehensive analytical characterization that takes into account Neu5Gc content, domain, and site-specific information like occupancy, glycan distribution, and sialic acid linkage. Strategies to minimize the Neu5Gc content should be adopted early in process development. A standardized reporting of Neu5Gc content should be adopted in order to facilitate risk assessments.